Ley Especial de Fomento para las Organizaciones No Gubernamentales de Desarrollo (ONDG) (La Revista de Derecho, 2013)
DOI: http://dx.doi.org/10.5377/lrd.v32i0.1256 Revista de Derecho, Vol. 32, Nº 1, Año 2011: 180-191